A joint water diversion plan for China. Issue 5 (1st May 2013) - Liang, Shumin
Abstract : To achieve domestic food security and help alleviate poverty, China is undertaking ambitious water transfer projects as a means of optimizing management of its water resources. This article proposes a three‐part approach to south‐to‐north water diversion in China. The plan consists of an extension to the current middle route, an alternative (and expanded) western route, and a trunk canal system to transfer water to the northwest. The proposed project would be undertaken in four stages; costs and benefits of each stage are included here. With the completion of the plan, the total annual capacity of south‐to‐north water diversion in China would be 238 × 10 9 m 3 . Total project investment is estimated at 3, 147 billion yuan (498 billion). Major benefits generated by the project include annual income of 287 billion yuan (45 billion) through sales of water and hydropower, addition of 44.3 × 10 6 ha (109 × 10 6 acres) of irrigated arable land, relocation of 66.5 × 10 6 inhabitants to newly irrigated regions, and conversion of 470, 000 km 2 (181, 468 sq mi) of desert to irrigated land and forest to provide wind shelter and preserve topsoil.